(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
In this work some ordering methods proposed for fuzzy numbers are explored. Furthermore, a proposal based on the abscissa of the centroid of each fuzzy number is presented. The proposed method is compared with another one that also uses the centroid calculation method, showing its improvements. This ordering method satisfies intuition in most cases, making it useful for database queries.